Synthesis of Deuterated Poly(4-acetoxystyrene) by a Polymer-analogous Reaction Sequence - Khalifa, M; Youssef ِA (Arab Journal for Sciences and Research Publishing, 2016)
This study describes a new simple method for preparing deuterated poly(4-acetoxystyrene). The new method offers cost-effective and alternative route to preparing deuterated polymers that otherwise have to be prepared from the deuterated monomers. Deuterated poly(4-acetylstyrene) (ACPS-d4) and poly(4-acetoxystyrene) (APS-d4) were synthesised from deuterated polystyrene under thermal reactions. The polystyrene-d5 (PS-d5) was acetylated using cyclohexane as solvent instead of carbon disulfide (a highly toxic and flammable solvent) and acetyl chloride as the acetylating agent. Using commercially available reagents, the acetyl group was converted to an acetoxy group by Baeyer-Villiger oxidation. The oxidation of ACPS was carried out with various agents and reaction conditions. The oxidation kinetics with peracetic acid was followed by FT-IR spectroscopy. The duterated polymers were characterised by nuclear magnetic resonance (NMR) and fourier transform infrared spectroscopy (FTIR). The optimised procedure will make future work using neutron scattering possible.